Exercise postconditioning reduces ischemic injury via suppression of cerebral gluconeogenesis in rats. Issue 1 (30th November 2022) - Li, Fengwu; Geng, Xiaokun; Ilagan, Roxanne; Bai, Shangying; Chen, Yuhua; Ding, Yuchuan
Abstract: Pre‐stroke exercise conditioning reduces neurovascular injury and improves functional outcomes after stroke. The goal of this study was to explore if post‐stroke exercise conditioning (PostE) reduced brain injury and whether it was associated with the regulation of gluconeogenesis. Adult rats received 2 h of middle cerebral artery (MCA) occlusion, followed by 24 h of reperfusion. Treadmill activity was then initiated 24 h after reperfusion for PostE. The severity of the brain damage was determined by infarct volume, apoptotic cell death, and neurological deficit at one and three days after reperfusion. We measured gluconeogenesis including oxaloacetate (OAA), phosphoenolpyruvate (PEP), pyruvic acid, lactate, ROS, and glucose via ELISA, as well as the location and expression of the key enzyme phosphoenolpyruvate carboxykinase (PCK)‐1/2 via immunofluorescence. We also determined upstream pathways including forkhead transcription factor (FoxO1), p‐FoxO1, 3‐kinase (PI3K)/Akt, and p‐PI3K/Akt via Western blot. Additionally, the cytoplasmic expression of p‐FoxO1 was detected by immunofluorescence. Compared to non‐exercise control, PostE (* p  < .05) decreased brain infarct volumes, neurological deficits, and cell death at one and three days. PostE groups (* p  < .05) saw increases in OAA and decreases in PEP, pyruvic acid, lactate, ROS, glucose levels, and tissue PCKs expression on both days. PCK‐1/2 expressions were also significantly (* p  < .05) suppressed by the exercise setting. Additionally, phosphorylated PI3K, AKT, and FoxO1 protein expression were significantly induced by PostE at one and three days (* p  < .05). In this study, PostE reduced brain injury after stroke, in association with activated PI3K/AKT/FoxO1 signaling, and inhibited gluconeogenesis. These results suggest the involvement of FoxO1 regulation of gluconeogenesis underlying post‐stroke neuroprotection. Abstract : In this study, PostE reduced brain injury after stroke, in association with activated PI3K/AKT/FoxO1 signals and inhibited gluconeogenesis. These results suggest the involvement of FoxO1 regulation of gluconeogenesis underlying post–stroke neuroprotection.